Comparative analysis of different foamy oil flow characteristics and production performances of two similar super-heavy oil reservoirs using microscopic visual physical experiments - Xue, Yongchao; Jia, Zhihao; Wang, Suran; Zhang, Xuze; Pu, Baobiao (Frontiers in Earth Science, 2023)
Foamy oil flow is a potentially important reason for enhanced oil recovery (EOR) in super-heavy oil reservoirs during depressurized cold production (DCP). M oil reservoir and H oil reservoir located in Venezuela are typical super-heavy oil reservoirs with the foamy oil flow stage, and the properties of two reservoirs are similar. However, the production performances between two reservoirs in the stage foamy oil flow is quite different. In this paper, the novel microscopic visual physical experiments for foamy oil flow have been carried out to determine the flow characteristics of foamy oil and production performance. Three production stages of DCP are divided: stage I (the pressure greater than bubble point pressure), stage II (the pressure ranging from pseudo bubble point pressure to bubble point pressure), and stage III (the pressure lower than pseudo bubble point pressure). Then, the effects of different foamy oil flow characteristics in each production stage on production performances are investigated using comparative analysis method. The results show that the flow characteristics of the oil in the M and H oil reservoirs are both single-phase flow at stage I of DCP and two-phase flow at stage III of DCP. However, a phenomenon of strong foamy oil flow appeared in M oil reservoir while a phenomenon of weak foamy oil flow appeared in H oil reservoir at stage II of DCP. For the production performance, the oil rate, cumulative oil production and cumulative gas production of M oil reservoir increased obviously, while which of H oil reservoir increased slowly. The reason for the difference between the two oil reservoirs is that the super-heavy oil of M oil reservoir has more dissolved GOR and asphaltene content compared to H oil reservoir, and the pressure and temperature of M oil reservoir are more suitable for strong foamy oil flow.